Efficient corrosion inhibition by sugarcane purple rind extract for carbon steel in HCl solution: mechanism analyses by experimental and in silico insights. Issue 50 (27th September 2021) - Meng, Siguang; Liu, Zining; Zhao, Xiaoqi; Fan, Baomin; Liu, Hao; Guo, Mao; Hao, Hua
Abstract : The anticorrosive mechanism of extracted components from sugarcane purple rind for carbon steel in HCl solution is clarified by weight loss, electrochemical and theoretical (novel DFT calculation and molecular dynamics simulation) analyses. Abstract : Sugarcane purple rind ethanolic extract (SPRE) was evaluated as an efficient corrosion inhibitor for carbon steel (C-steel) in 1 M HCl solution. Dynamic weight loss, potentiodynamic polarization, electrochemical impedance spectroscopy (EIS) and frequency modulation (EFM) measurements were employed to evaluate the anticorrosive efficiency of SPRE, which was further validated by morphological and wettability analyses. The results of the weight loss tests showed that the inhibition efficiency ( η w ) for C-steel in HCl solution increased with an increase in the concentration of SPRE. An increase in temperature moderately impaired the anticorrosive efficacy of SPRE. The maximum η w of 96.2% was attained for C-steel in the inhibition system with 800 mg L −1 SPRE at 298 K. The polarization curves indicated that SPRE simultaneously suppressed the anodic and cathodic reactions for C-steel in HCl solution, which can be categorized as a mixed-type corrosion inhibitor with a predominant anodic effect. The corrosion current density ( i corr-P ) was monotonously reduced with an increase in the concentration of SPRE. The charge transfer resistance ( R ct ) was enhanced for C-steel in the inhibition solution with a restrained capacitive property due to the adsorption of SPRE. A high temperature caused partial desorption of SPRE on the C-steel surface and a slight increase in i corr-P and decrease in R ct . However, SPRE still fully maintained its morphology and wettability at 328 K. The electrochemical kinetics of C-steel in HCl solution without and with SPRE was also supported by EFM spectra. The adsorption of SPRE conformed to the Langmuir isotherm and increased the corrosion activation energy of C-steel. Complementing the experimental observations, calculations based on density functional theory indicated that the hydroxyl-substituted pyran moiety on the carthamin (CTM) and anthocyanin (ATC) constituents in SPRE hardly contributed to its reactive activity due to their adsorption processes. Therefore, CTM and ATC exhibited imperfect parallel adsorption on the Fe (100) plane according to the molecular dynamics simulation, while anthoxanthin (ATA) and catechinic acid (CCA) constituents exhibited a flat orientation on the iron surface.